A Typical Point Rainfall Analysis of the Soil Conservation Centre Kota - Roy, K.; Khybri, M. L.; Handa, D. P. (Indian Forester, 1970)
Rainfall frequency data over a period of 12 years from 1956 to 1967 of an automatic recording raingauge at the Soil Conservation Research, Demonstration and Training Centre, Kota, have been analysed and discussed in this paper. The curve indicating the rainfall-intensities and durations have been drawn after analysing the data which yield a family of parallel curves. The general equation representing the curves for the region is given by: I = K/(t+a)d; where, I = Rainfall intensity in inches/hr. t = Duration in minutes; and, K, a and d are constants. The values of K, a and d have been worked out for different frequency periods.